The fevers of the puerperium - Greenwood, Alan Young (The University of Edinburgh, 1906)
Much that has been written on the prevention of puerperal sepsis mag seem superfluous, and possibly is, but it is only by thoroughly understanding how the sepsis is incurred that one realises how necessary it is to take every possible precaution.

The Midwives Act of 1902 has done, and will do more to prevent the mortality in this class of diseases. I well remember the astonishment of a newly enrolled midwife after the first visit of the Lady Inspector.

"She told me I had to get print washing dresses: with a puzzled look of wonderment, and she one of the best midwives in the district! Much other goodly and necessary advice do these Lady Inspectors administer to the midwives, which before long is sure to bear goo fruit.

What have we gained during recent years in the knowledge of puerperal sepsis? We have ascertained that the primary cause is organismal infection, and that the streptococci are the most powerful organisms. We have discovered the great curative method of Serum-therapy, and we are concluding, rightly or wrongly hat because it is absolutely curative in diphtheria it ought to be the same in all infective disease. For my part, while agreeing with many others that antistreptococcus serum is of benefit in many cases, and perhaps should be given a trial in all serious cases, I cannot conceive considering the variety of strains of streptocci, and of other organisms associa- with them in septic conditions,of a serum which could possibly be a specific cure for puerperal sepsis.

We hake yet to find some condition (or conditions) of which we are at present ignorant, which makes the parturient woman so susceptible to bacterial invasion, apart from the open wound and the proximity of the peritoneum. If one could ascertain the significance of the leucocytosis of pregnancy, we possibly would have a clue to the secret.